Analgesic and Antidiarrheal Activities of Leaf of Podocarpus neriifolius D. Don - Razan, Md Rahatullah; Rahman, Muhammed Mahfuzur; Tahia, Faiza; Hossain, Md Khalid; Rashid, Mohammad A (Bangladesh Pharmaceutical Journal, 2016)
The methanol extract of leaf of Podocarpus neriifolius D. Don exhibited in vivo peripheral analgesic and antidiarrheal activities in Swiss Albino mice. In the peripheral analgesic activity assay, the methanolic extract showed 50.00 ± 8.57% and 70.25 ± 1.18% inhibition of acetic acid-induced writhing at 200 and 400 mg/kg body weight, respectively. In addition, the extract also revealed a dose dependant inhibition of castor oil- induced diarrhea with 43.77 ± 3.13% and 56.23 ± 6.49% inhibition of feces at 200 and 400 mg/kg body weight, respectively Bangladesh Pharmaceutical Journal 19(2): 215-218, 2016